2019
DOI: 10.24036/103915-019883
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Keterampilan Membaca Pemahaman Dan Keterampilan Menulis Teks Laporan Hasil Observasi Siswa Kelas Vii SMP Negeri 4 Pariaman

Abstract: This research focus on the describing skill correlation of reading understanding and skill text writing report observation results of the seventh grade students of SMP Negeri 4 Pariaman. This type of research is quantitative research with correlational methods. The sample of this research is students of SMP Negeri 4 Pariaman amounted 42 students. The data of this research are  the score of the reading comprehension skill test results and  the score of the test results in the writing skills of the report text o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…Dalam proses pembelajaran di sekolah pengajaran membaca harus memperoleh perhatian yang serius dari pendidik bahasa Indonesia. Menurut Vygotsky (dalam Putri, at al, 2019), guru dapat membantu mengembangkan kemampuan membaca pemahaman siswa dalam kelas serta memberikan dukungan, bantuan, dan kepercayaan diri siswa. Melalui pengajaran membaca, pendidik mengarahkan peserta didiknya, agar mampu dalam memahami isi bacaan ( Sari, et al, 2018).…”
Section: Kata Pengantarunclassified
“…Dalam proses pembelajaran di sekolah pengajaran membaca harus memperoleh perhatian yang serius dari pendidik bahasa Indonesia. Menurut Vygotsky (dalam Putri, at al, 2019), guru dapat membantu mengembangkan kemampuan membaca pemahaman siswa dalam kelas serta memberikan dukungan, bantuan, dan kepercayaan diri siswa. Melalui pengajaran membaca, pendidik mengarahkan peserta didiknya, agar mampu dalam memahami isi bacaan ( Sari, et al, 2018).…”
Section: Kata Pengantarunclassified
“…This critical and contextual way of thinking affects later on learning Indonesian, so that environmental education and language learning are interrelated. Putri and Syahrul (2019) revealed that in learning in the school environment, teaching reading must receive serious attention from educators in Indonesia. Through teaching, educators are able to direct students in language learning.…”
mentioning
confidence: 99%
“…Sehingga pemanfaatan lingkungan bisa dijadikan media dalam metode pembelajaran. Putri et al (2019) mengungkapkan bahwa dalam pembelajaran di lingkungan sekolah, pengajaran membaca harus memperoleh perhatian yang serius dari pendidik di Indonesia. Melalui pengajaran, pendidik mampu mengarahkan peserta didik dalam pembelajaran bahasa.…”
unclassified